Perceived parental relationship quality and adolescent conscious bias: important links between affect, agency, gender, and race/ethnicity - Terrell, Amanda; Merten, Michael J.; Wickrama, Thulitha (Frontiers in Psychology, 2025)
IntroductionGuided by attachment, social cognitive, and ecological systems theories, this study examined the direct and indirect effects of perceived parent-adolescent relationship quality on youths' conscious bias toward individuals facing socioeconomic or minority-related challenges.MethodsData were collected from 702 U.S. 18-year-olds via Qualtrics online panels. Measures included parent relationship quality, negative affect, human agency, and conscious bias (disregard for minority experiences and blaming attitudes).ResultsThe findings revealed that strong parent-teen bonds indirectly influenced conscious bias through psychosocial wellbeing. However, while negative emotions were universally influential, the impact of human agency varied depending on gender and race/ethnicity.DiscussionStudy findings underscore the necessity for a more comprehensive understanding of human agency as personal empowerment, considering gendered socialization practices and cultural nuances across different racial/ethnic groups. Additionally, there is an important need to integrate diversity, equity, and inclusion principles into parental education initiatives.